A Systematic Review and Meta-analysis of Antibiotic Treatment Duration for Bacteremia Due to Enterobacteriaceae - Tansarli, Giannoula S. (Antimicrob Agents Chemother, 2019)
The duration of antibiotic therapy for bacteremia due to Enterobacteriaceae is not well defined. We sought to evaluate the clinical outcomes with shorter- versus longer-course treatment. We performed a systematic search of the PubMed and EMBASE databases through May 2018. Studies presenting comparative outcomes between patients receiving antibiotic treatment for ≤10 days (“short-course”) and those treated for >10 days (“long-course”) were considered eligible. Four retrospective cohort studies and one randomized controlled trial comprising 2,865 patients met the inclusion criteria. The short- and long-course antibiotic treatments did not differ in 30-day all-cause mortality (1,374 patients; risk ratio [RR] = 0.99; 95% confidence interval [CI], 0.69 to 1.43), 90-day all-cause mortality (1,750 patients; RR = 1.16; 95% CI, 0.81 to 1.66), clinical cure (1,080 patients; RR = 1.02; 95% CI, 0.96 to 1.08), or relapse at 90 days (1,750 patients; RR = 1.08; 95% CI, 0.69 to 1.67). In patients with bacteremia due to Enterobacteriaceae, the short- and long-course antibiotic treatments did not differ significantly in terms of clinical outcomes. Further well-designed studies are needed before treatment for 10 days or less is adopted in clinical practice.